UNHEARD SENTIMENTS OF MAMANWA (INDIGENOUS) LEARNERS IN THE MAINSTREAM EDUCATION: A BASIS FOR EDUCATIONAL POLICY - Oclarit Jr., Federico P; Betarmos Jr., Vicente S; Casinillo, Leomarich F (Sanata Dharma University Yogyakarta, 2023)
This article aimed to investigate the unheard sentiments among Mamanwa learners in mainstream education to create a suitable educational policy for indigenous learners in the Philippines. The study utilized purposive (non-probability) sampling comprising fifteen participants residing in Panaon Area, Southern Leyte, Philippines. Since the study involved the indigenous people community, free prior informed consent (FPIC) was secured from authorities. This study focused on the lived experiences of Mamanwa learners, particularly the barriers, challenges, and coping mechanisms for handling the struggles they faced in mainstream education. A face-to-face semi-structured interview was employed to gather meaningful responses analyzed through Colaizzi's strategy. The findings revealed that the Mamanwa learners' social isolation, the inadequacy of learning materials, lack of access to educational services, and limited support resources and educational funds from the government have contributed to their ongoing challenge to completion in mainstream education. These factors have all affected their personal and social well-being. Conclusively, despite the barriers and challenges, however, the Mamanwa learners are becoming resilient and diversely unique individuals who need to be understood, accepted, and embraced just like any other member of society. Furthermore, the fueling mechanisms of every indigenous group to cross mainstream education are in the hopes of building growth, promoting connections through intense exposure in the community, and as individuals of disadvantaged groups with a social change mindset aimed to improve their social status.